Cry It Out: What Is It and Is It Appropriate?. Issue 3 (May 2017) - Beal, Judy A.
Abstract : Infant wakefulness at night is common. New parents often turn to the Internet for what to do when they encounter issues with their new baby that they're not sure how to handle, however, there are multiple websites offering advice that is not evidence-based. Our pediatric nursing expert, Dr. Beal, provides the most recent information on infant wakefulness at night for nurses to be able offer helpful advice to parents.